Teaching English to Pakistani Mainstream School Dyslexic Students through Computer-Assisted Reading Materials - Muhammad Asif Ikram Anjum; Zahida Mansoor (Linguistics and Literature Review, 2020)
The present research aims at investigating the potential of indigenously developed computer-assisted reading materials for teaching the English language to dyslexic students of elementary level in Pakistani mainstream schools. In doing this, grade VI students from a public school were screened using the Learning Disabilities Checklist. Twenty purposively selected participants with a checklist score of 50% or more formed the study sample. Computer-assisted reading materials were designed in the light of Mayer’s (2005) Cognitive Theory of Multimedia Learning. A two-week treatment was administered to the students in the computer lab of a public high school. Data collected from the pretest and post-test scores of the participants were analyzed using descriptive statistics and paired sample t-test. The study’s findings reveal the efficacy of specifically designed computer-assisted reading materials for teaching the English language to Pakistani mainstream school dyslexic students of elementary level.